Field Evaluation in the Intelligence and Counterintelligence Context: Workshop Summary - National Research Council (The National Academies Press, 2010)
On September 22-23, 2009, the National Research Council held a workshop on the field evaluation of behavioral and cognitive sciences—based methods and tools for use in the areas of intelligence and counterintelligence. Broadly speaking, the purpose of the workshop was to discuss the best ways to take methods and tools from behavioral science and apply them to work in intelligence operations. More specifically, the workshop focused on the issue of field evaluation—the testing of these methods and tools in the context in which they will be used in order to determine if they are effective in real-world settings.
Keywords: Behavioral and Social Sciences; Conflict and Security Issues

Challenges and Opportunities in Using Residual Newborn Screening Samples for Translational Research: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Newborn screening samples are used to test more than 4 million infants each year for life-threatening diseases that are treatable if found at birth. These specimens also represent a potentially invaluable resource for public health and biomedical research. The IOM held a workshop to examine issues surrounding the use of residual specimens for translational research.
Keywords: Health and Medicine

Regionalizing Emergency Care: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
During medical emergencies, hospital staff and emergency medical services (EMS) providers, can face barriers in delivering the fastest and best possible care. Overcrowded emergency rooms cannot care for patients as quickly as necessary, and some may divert ambulances and turn away new patients outright. In many states, ambulance staff lacks the means to determine which hospitals can provide the best care to a patient. Given this absence of knowledge, they bring patients to the closest hospital. In addition, because emergency service providers from different companies compete with each other for patients, and emergency care legislation varies from state to state, it is difficult to establish the necessary local, interstate, and national communication and collaboration to create a more efficient system.
Keywords: Health and Medicine

Statistical Modeling of Cement Heat of Hydration Using Phase and Fineness Variables - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 167: Statistical Modeling of Cement Heat of Hydration Using Phase and Fineness Variables explores alternative predictive models for seven-day cement heat of hydration.
Keywords: Transportation and Infrastructure

Persistent Forecasting of Disruptive Technologies—Report 2 - National Research Council (The National Academies Press, 2010)
The term "disruptive technology" describes a technology that results in a sudden change affecting already established technologies or markets. Disruptive technologies cause one or more discontinuities in the normal evolutionary life cycle of technology. This may lead to an unexpected destabilization of an older technology order and an opportunity for new competitors to displace incumbents. Frequently cited examples include digital photography and desktop publishing.
Keywords: Engineering and Technology

Review of the Proposal for the Gulf Long-Term Follow-Up Study: Highlights from the September 2010 Workshop: Workshop Report - Institute of Medicine (The National Academies Press, 2010)
The Gulf of Mexico oil spill is unprecedented not only in its size but also in the use of chemical dispersants and controlled burns to remove the oil. The National Institute of Environmental Health Sciences (NIEHS) is designing a study to investigate the health effects on clean-up workers. The IOM held a workshop to review and comment on NIEHS'o;s study protocol.
Keywords: Environment and Environmental Studies

Providing Healthy and Safe Foods As We Age: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Does a longer life mean a healthier life? The number of adults over 65 in the United States is growing, but many may not be aware that they are at greater risk from foodborne diseases and their nutritional needs change as they age. The IOM's Food Forum held a workshop October 29-30, 2009, to discuss food safety and nutrition concerns for older adults.
Keywords: Food and Nutrition; Health and Medicine

Forging the Future of Space Science: The Next 50 Years - National Research Council (The National Academies Press, 2010)
From September 2007 to June 2008 the Space Studies Board conducted an international public seminar series, with each monthly talk highlighting a different topic in space and Earth science. The principal lectures from the series are compiled in Forging the Future of Space Science. The topics of these events covered the full spectrum of space and Earth science research, from global climate change, to the cosmic origins of life, to the exploration of the Moon and Mars, to the scientific research required to support human spaceflight.
Keywords: Space and Aeronautics

The Value of Genetic and Genomic Technologies: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Knowing one's genetic disposition to a variety of diseases, including common chronic diseases, can benefit both the individual and society at large. The IOM's Roundtable on Translating Genomic-Based Research for Health held a workshop on March 22, 2010, to bring together diverse perspectives on the value of genetic testing, and to discuss its use in clinical practice.
Keywords: Health and Medicine

A Foundation for Evidence-Driven Practice: A Rapid Learning System for Cancer Care: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
The IOM's National Cancer Policy Forum held a workshop October 5-6, 2009, to examine how to apply the concept of a 'rapid learning health system' to the problem of cancer. This document summarizes the workshop.
Keywords: Health and Medicine

Certifiably Sustainable?: The Role of Third-Party Certification Systems: Report of a Workshop - National Research Council (The National Academies Press, 2010)
Consumption of goods and services represents a growing share of global economic activity. In the United States, consumption accounts for more than two-thirds of gross domestic product. This trend of increasing consumption has brought with it negative consequences for the environment and human well-being. Global demand for energy, food, and all manner of goods is on the rise, putting strains on the natural and human capital required to produce them. Extractive industries and production processes are prominent causes of species endangerment. Modern economies are underpinned by substantial energy consumption, a primary contributor to the current climate crisis. Expanding international trade has led to many economic opportunities, but has also contributed to unfair labor practices and wealth disparities.
Keywords: Environment and Environmental Studies

Managing Increasing Ridership Demand - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Transit Cooperative Research Program (TCRP) Research Results Digest 96: Managing Increasing Ridership Demand documents a 2009 study mission to Guayaquil, Ecuador; Santiago, Chile; Buenos Aires, Argentina; and Porto Alegre, Brazil, that investigated how transit operators and agencies in these cities accommodated sudden and significant growth in the number of riders and increasing demand for service.
Keywords: Transportation and Infrastructure

Demographic Changes, a View from California: Implications for Framing Health Disparities: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
The IOM held a workshop on July 28, 2008, to examine strategies for discussing health disparities in ways that engage the public and motivate change. Speakers focused on health disparities in California, which continues to see dramatic demographic shifts.
Keywords: Health and Medicine

Describing Socioeconomic Futures for Climate Change Research and Assessment: Report of a Workshop - National Research Council (The National Academies Press, 2010)
The implications of climate change for the environment and society depend on the rate and magnitude of climate change, but also on changes in technology, economics, lifestyles, and policy that will affect the capacity both for limiting and adapting to climate change. Describing Socioeconomic Futures for Climate Change Research and Assessment reviews the state of science for considering socioeconomic changes over long time frames and clarifies definitions and concepts to facilitate communication across research communities. The book also explores driving forces and key uncertainties that will affect impacts, adaptation, vulnerability and mitigation in the future. Furthermore, it considers research needs and the elements of a strategy for describing socioeconomic and environmental futures for climate change research and assessment. Describing Socioeconomic Futures for Climate Change Research and Assessment explores the current state of science in scenario development and application, asserting that while little attention has been given to preparing quantitative and narrative socioeconomic information, advances in computing capacity are making development of such probabilistic scenarios a reality. It also addresses a number of specific methodological challenges and opportunities and discusses opportunities for a next round of assessments.
Keywords: Environment and Environmental Studies; Earth Sciences

The Teacher Development Continuum in the United States and China: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
In 1999, Liping Ma published her book Knowing and Teaching Elementary Mathematics: Teachers' Understanding of Fundamental Mathematics in the United States and China, which probed the kinds of knowledge that elementary school teachers need to convey mathematical concepts and procedures effectively to their students. Later that year, Roger Howe, a member of the U.S. National Commission on Mathematics Instruction (USNC/MI), reviewed the book for the Notices of the American Mathematical Society, concluding that it 'has lessons for all educational policymakers.'
Keywords: Education

Marketing Guidebook for Small Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Airport Cooperative Research Program (ACRP) Report 28: Marketing Guidebook for Small Airports explores development of a marketing program for general aviation or commercial service airports on a small or minimal budget.View information about the TRB webinar on ACRP Report 28: Marketing Guidebook for Small Airports Tuesday, April 6, 2010 at 2 PM EDT.The November 2013 ACRP Impacts on Practice highlights how the Fort Wayne International Airport in Indiana used ACRP Report 28 to create a marketing plan.
Keywords: Transportation and Infrastructure

Exploring the Intersection of Science Education and 21st Century Skills: A Workshop Summary - National Research Council (The National Academies Press, 2010)
An emerging body of research suggests that a set of broad "21st century skills"—such as adaptability, complex communication skills, and the ability to solve non-routine problems—are valuable across a wide range of jobs in the national economy. However, the role of K-12 education in helping students learn these skills is a subject of current debate. Some business and education groups have advocated infusing 21st century skills into the school curriculum, and several states have launched such efforts. Other observers argue that focusing on skills detracts attention from learning of important content knowledge.
Keywords: Education

Airport Energy Efficiency and Cost Reduction - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2010)
TRB’s Airport Cooperative Research Program (ACRP) Synthesis 21: Airport Energy Efficiency and Cost Reduction explores energy efficiency improvements being implemented at airports across the country that are low cost and short payback.
Keywords: Transportation and Infrastructure

New Worlds, New Horizons in Astronomy and Astrophysics - National Research Council (The National Academies Press, 2010)
Driven by discoveries, and enabled by leaps in technology and imagination, our understanding of the universe has changed dramatically during the course of the last few decades. The fields of astronomy and astrophysics are making new connections to physics, chemistry, biology, and computer science. Based on a broad and comprehensive survey of scientific opportunities, infrastructure, and organization in a national and international context, New Worlds, New Horizons in Astronomy and Astrophysics outlines a plan for ground- and space- based astronomy and astrophysics for the decade of the 2010's. Realizing these scientific opportunities is contingent upon maintaining and strengthening the foundations of the research enterprise including technological development, theory, computation and data handling, laboratory experiments, and human resources. New Worlds, New Horizons in Astronomy and Astrophysics proposes enhancing innovative but moderate-cost programs in space and on the ground that will enable the community to respond rapidly and flexibly to new scientific discoveries. The book recommends beginning construction on survey telescopes in space and on the ground to investigate the nature of dark energy, as well as the next generation of large ground-based giant optical telescopes and a new class of space-based gravitational observatory to observe the merging of distant black holes and precisely test theories of gravity. New Worlds, New Horizons in Astronomy and Astrophysics recommends a balanced and executable program that will support research surrounding the most profound questions about the cosmos. The discoveries ahead will facilitate the search for habitable planets, shed light on dark energy and dark matter, and aid our understanding of the history of the universe and how the earliest stars and galaxies formed. The book is a useful resource for agencies supporting the field of astronomy and astrophysics, the Congressional committees with jurisdiction over those agencies, the scientific community, and the public.
Keywords: Space and Aeronautics

Monitoring Climate Change Impacts: Metrics at the Intersection of the Human and Earth Systems - National Research Council (The National Academies Press, 2010)
The stresses associated with climate change are expected to be felt keenly as human population grows to a projected 9 billion by the middle of this century, increasing the demand for resources and supporting infrastructure. Therefore, information to assess vulnerabilities to climate change is needed to support policies and investments designed to increase resilience in human and Earth systems.
Keywords: Environment and Environmental Studies; Earth Sciences